Un golpe al corazón de la violencia: Yuri Herrera (Altre Modernità, 2018)
In Eduardo Antonio Parra’s opinion, most of the mexican writers that narrate about drug trafficking cartels focus it as a complement or circustantial support of their stories and characters. Yuri Herrera’s Trabajos del reino does it instead the direct way, trough a talented narcocorridos-song writer, who works for a drug lord. His artist eyes disarmed the “vida narca” glamour, making visible his psychic violence in a literary purpose that flee, intentionally, from the common places of the theme, contributing to the awareness and denounce with the discourse and language of the “contramaquina”.